Macam Varietas Tanaman Selada Perlakuan Media Organik - Dewi, Sinta; Hadi, Pramono; Widiastuti, Libria; Ihsan, Mohamad (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
This research seeks to assess how organic and varietal planting media impact the growth and yield of lettuce plants (Lactuca sativa. L). The study was conducted using the Complete Group Random Design (CGRD) method with two treatment factors. The first factor involved three types of organic planting media: (M1) a blend of soil, manure, and burnt husks; (M2) a blend of soil, manure, and cocopeat; (M3) a blend of soil, manure, burnt husks, and cocopeat. The second factor comprised three varieties: (V1) Grand Rapid green lettuce, (V2) Red Rapid red lettuce, and (V3) Lollo Rossa red lettuce. The findings indicate that treatment (M3), consisting of soil, manure, burnt husks, and cocopeat, influences leaf width, plant weight, and dry stash weight. The best yield was observed in treatment (V1) with the Grand Rapid green lettuce variety showing significant effects across all parameters. The conclusions are as follows: 1. Organic growing media does not affect all observation parameters related to the growth and yield of lettuce plants. 2. Varietal differences have a noticeable impact on all observation parameters related to lettuce growth and yield. 3. The interaction between organic growing media and plant varieties significantly affects the observation parameters of plant height and plant weight, while it does not affect leaf width and dry stash weight.